English Summaries - Redaktion (Peripeti, 2022)
Connected Matters: Collaboration and Care in Nana Francisca Schottländer’s Bodyscaping By Solveig Gade This article is preoccupied with the dramaturgies and collaborations between human and more-than-human agents in contemporary eco-performance. Putting Anna Tsing’s concept of contamination as collaboration as well as Maria Puig de la Bellacasa’s notion of care time into dialogue with theatre and performance studies, the article investigates Danish choreographer Nana Fransisca Schottländer’s performance Bodyscaping, arguing that contemporary eco-performance does not only represent, but also practice care. Jessie Kleemann’s Art of Survival By David W. Norman In her work as an educator, actor, poet and visual artist, Jessie Kleemann has persistently expanded the limits of arts discourse in Kalaallit Nunaat, not least through her unique approach to body art informed by historical Kalaallit theatrical forms and antimimetic dramaturgy. Emphasizing how Kleemann’s embodied practice prompts reflection on the potential for action amid environmental collapse, this essay situates her work alongside schools of thought that have theorized the body during moments of crisis. I focus on Kleemann’s early experimentation with analog video and recent ecocritical poetry, aligning her work with traditions ranging from ancestral Inuit performance genres to post-1945 action art and contemporary practices advocating on behalf of missing and murdered Indigenous women and girls. Kleemann’s methods, refracted through these traditions, place embodied action at the center of efforts to form more ethical relations. The Art of Sustainability By Sarah Woods As the systems thinker Fritjof Capra points out, through the course of Western history we have tended to give more attention to elements or things than to interconnections or relationships, thinking more mechanistically than holistically, asking “What is it made of?” rather than “What is the pattern?” 26. Sometimes, however, the study of patterns and relationships comes to the fore. Now, in our networked, digital world, as we wrestle with some of the 66 continuous problems that Donella Meadows and her team addressed in the classic Limits to Growth27, like climate change, global inequality and migration, is one of those times. This article shows the diverse and multi-fold advantages of using systems thinking as a methodology for working creatively with complexity. It explores the basic biological patterns that define life; the nature, patterns and effects of different forms of feedback; and how systems thinking can assist us in problem-solving, managing complexity and in understanding how creativity works. Living sustainably means living within the finite limits of our system. Understanding more about the systems we live with, whether through taking action on climate change or creating a well-functioning piece of art, helps us to live well and to create well. The Slow Integration of Sustainability into Contemporary Theatre and Performance Practices in Cameroon By Kenneth T. Nsah, Lisette N. Malung and Noella M. Ngunyam The Cameroonian theatre landscape, both Anglophone and Francophone, is not left untouched by current concerns and discourses about climate change, ecological degradation, and particularly environmental/natural sustainability. In this article, we will examine the emerging inclusion of sustainability in theatre and performances in Cameroon. Specifically, we will discuss the ways in which choices of costumes, makeup, stage props, and occasionally thematics reflect and seek to promote the sustainable management of Nature. Methodologically, we will employ data gathered from five current theatre troupes in Cameroon, interviews conducted with some theatre directors and practitioners, and the personal experiences of (some) co-authors who are also theatre practitioners. We will begin by discussing some unsustainable practices that characterised much of previous Cameroonian theatrical performances and then proceed to present the evolution of the situation, especially as demonstrated in the choices and deployment of costumes, makeup, stage props, and thematics in a selection of theatre performances and theatre scripts. In this way, we hope to highlight the contribution of Cameroonian theatre towards ensuring a just and sustainable planet Earth for all. Costume and Sustainability: From Past Practice to Future Strategies for an Ecological Costume Praxis By Sofia Pantouvaki, Ingvill Fossheim and Susanna Suurla What can we learn from past traditions and what sustainability practices are currently employed in the field of costume? Moving towards a more ecological costume creation, there is an increasing need to address the responsibility of the costume practitioners through the lifecycle of costume from design to production. This article provides an overview of current sustainable costume practices and suggests that it is timely to rethink costume praxis from an ecologically responsible perspective. The article addresses the necessity of embedding ecological equity into all aspects of costume creation and proposes that a resilient ecosystem of costume practice can be envisioned within professional institutions, as well as the individual costume designer. Seeking Performance Sustainability within Disability By Molly Joyce The disability community has traditionally been left out of sustainability conversations. Disability is often seen as a “blind spot” in such frameworks (Miethlich 2019) and is not considered part of sustainability metrics (Beyond Green,2019). Therefore, it is pertinent to investigate what sustainability can manifest within the institutional and aesthetic circumstances of disability arts, specifically through the lens of disabled artists across performative disciplines. Leave No Bodymind Behind: Sins Invalid’s Vision of Crip Sustainability By Nina Muehlemann This article discusses how the work of US-collective Sins Invalid, particularly the 2021 documentary Loving with Three Hearts and 2020 performance piece We Love Like Barnacles, addresses the exclusion of disabled people, especially multiply marginalised disabled people, in discourses and practices that address ecological disaster. The article argues that the company positions ableism as a crucial part of said exclusion and with their work proposes a version of sustainability that is rooted in collective access and care.